E-Filantropi Pembiayaan Pendidikan: Gerakan Altruisme dalam Pemberdayaan Masyarakat Perbatasan di Tengah Pandemi Covid-19: E-Philanthropy in Education Financing: Altruism Movement in Empowering Border Communities amidst the Covid-19 Pandemic - Wildani Hefni (Jurnal Bimas Islam, 2021)
This article examines a new pattern of humanitarianism through digital technology, known as e-philanthropy. The utilization of digital space with social media has become an e-philanthropy concept amidst the covid-19 pandemic that happened to all levels of society. This study used a qualitative descriptive with virtual ethnographic methods. The object of this research is a program of #beasiswaArjuna, Pondok Pendawa, Bogor that implemented the altruism movement by collecting online donations to finance education for border communities. This article shows that philanthropy has shifted from conventional to digital forms, especially amidst the covid-19 pandemic. E-philanthropy manifests as an altruism movement in strengthening humanitarian solidarity by eliminating all selfishness and helping border communities to continue their education. The practice of philanthropy in the altruism movement amidst the covid-19 pandemic calls everyone to engage in altruistic actions to create happiness for everybody.